Master’s Programs in Russia: Four Paths of Future Development - O. V. Petrova; O. R. Chepyuk; S. D. Makarova; V. V. Mariko; A. I. Gorylev (Высшее образование в России)
The publication raises the question of the role of master’s degree in the system of modern higher education. Based on a survey of opinions (three-party survey) of key stakeholder groups (employers; students in higher education programs; managers of master’s degree programs; master’s degree teachers), the authors consider possible options for developing master’s degree as one of the key stages of higher education in Russia. The authors conclude that university development programs in the field of master’s degree education should be designed taking into account the high level of uncertainty in the external environment, which means that they should provide for scenario modeling of the future of the entire scientific and educational ecosystem. The study uses the classification of four types of the future labor market (“technological world”, “world of social responsibility”, “world of entrepreneurship” and “world of corporations”) as the main hypothesis about the options for such scenario planning. The study results are visualized in the form of a roadmap for the strategic development of the Russian master’s degree programs, highlighting key trends for each of the development options. The practical result of the study was the identification of the main “gaps” in the positions of stakeholders on the status of the master’s degree program and effective models of its implementation. The conclusions and results of the publication will be interesting for the purposes of the university strategic management, the formation of a development strategy for the master’s degree, as well as the development of special programs for interaction with employers and students.